Quaternary climates, environments, and magnetism - Maher, Barbara A. (Barbara Ann), 1960-; Thompson, Roy, 1948 August 23- (Cambridge University Press, 1999)
This volume presents an account of the uses of magnetic measurements in the environmental geosciences. It focuses on the Quaternary geological period and reviews the application of magnetic studies to climatic and environmental problems. The book is aimed at research scientists, graduates and advanced undergraduates.